Bean common (BCMV) and bean common mosaic necrosis (BCMNV) potyvirus in relation to bean landraces in the basque country - Ruiz de Galarreta, J.I=700 1 Perez de San Roman, C.; Abad, J.M.; Legorburu, F.J.
(Es, En)
ilus., 12 ref.
Keywords: POTYVIRUS DEL MOSAICO COMUN FRIJOL; NECROSIS; PHASEOLUS VULGARIS; ESPAÑA